GROWTH AND SURVIVAL RATE OF NILEM (Osteochilus hasselti) ON DIFFERENT STOCKING DENSITY - M. Alya Rizaqi; Mulyadi '; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from April 10 until june 10, 2015. The purpose of this study was to determine the different stocking densities for growth and survival rate of nilem (Osteochilus hasselti). The experiment was designed using Completely Random Design with three treatments and three replications. The treatment were applied, namely P1 of 5 tail/m3, P2 of 10 tail/m3, P3 of 15 tail/m3. The best results showed that stocking density of 10 tail/m3. Total absolute body weight, absolute body length, daily growth rate and survival rate was 4,68 grams, 3,07cm, 1,25 %/day and 93,33 % respectively. Water quality parameters were recorded namely temperature is 26–290 C, pH 6-7 and dissolved oxygen (DO) from 6,2 to 6,7 ppm/l.Keyword : Growth, Survival, Nilem (Osteochilus hasselti), Stocking Density